Allele *2 of the HS1, 2A enhancer of the Ig regulatory region associates with rheumatoid arthritis. Issue 3 (24th October 2008) - Tolusso, B; Frezza, D; Mattioli, C; Fedele, A L; Bosello, S; Faustini, F; Peluso, G; Giambra, V; Pietrapertosa, D; Morelli, A; Gremese, E; De Santis, M; et al.
Abstract : Objective: To investigate the role of the HS1, 2 enhancer polymorphisms as a new candidate marker for rheumatoid arthritis (RA) and to define the possible association with autoantibody positivity and clinical outcome. Methods: Genomic DNA was obtained from two cohorts of patients with RA (100 with early RA (ERA) and 114 with longstanding RA (LSRA)) and from 248 gender-matched controls from the same geographical area. Clinical and immunological characteristics were recorded for all the patients. Results: The percentage of the 2/2 genotype was higher in patients with ERA (27.0%), and in patients with LSRA (34.2%), than in controls (14.9%) (ERA: OR = 2.11 (95% CI 1.20 to 3.70) vs controls; LSRA: OR = 2.96 (95% CI 1.76 to 5.00) vs controls). A lower representation of allele *3 was present in patients with ERA (2.0%) than in controls (6.0%; OR = 0.32 (95% CI 0.11 to 0.91)). No significant associations were found between polymorphisms and autoantibodies positivity. Conclusion: The HS1, 2A allele *2 associates with early and longstanding RA.